2017
DOI: 10.1021/acs.analchem.6b02426
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screening Method for New Psychoactive Substances of Forensic Interest: Electrochemistry and Analytical Determination of Phenethylamines Derivatives (NBOMe) via Cyclic and Differential Pulse Voltammetry

Abstract: ABSTRACT:The NBOMe derivatives are phenethylamines derived from the 2C class of hallucinogens. Only a few human pharmacologic studies have been conducted on these drugs and several cases of intoxication and deaths have been reported. Presently, NBOMe are not a part of the routine drugs-of-abuse screening procedure for many police forces and there are no rapid immunoassay screening tests that can detect the presence of those compounds. In this paper, the voltammetric behavior of 25B NBOMe and 25I NBOMe were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 30 publications
2
19
0
3
Order By: Relevance
“…S2 †) illustrated that these compounds have two distinct oxidation peaks; peak I (E 1 z +0.815 V) and peak II (E 2 z +1.017 V), using screen printed graphite electrodes (SPEs) vs. Ag/AgCl reference electrode (scan rate: 50 mV s À1 ). The electrochemical oxidation mechanism of NBOMes was explained in detail by Andrade et al 43 Briey, the rst observed oxidation peak (peak I) develops as a result of the oxidation of the secondary amine into a primary amine. Whilst, the second oxidation peak (peak II) occurs due to the replacement of the halogen atom in the NBOMe compounds by a hydroxyl group, which aerwards produces a ketone.…”
Section: Resultsmentioning
confidence: 99%
“…S2 †) illustrated that these compounds have two distinct oxidation peaks; peak I (E 1 z +0.815 V) and peak II (E 2 z +1.017 V), using screen printed graphite electrodes (SPEs) vs. Ag/AgCl reference electrode (scan rate: 50 mV s À1 ). The electrochemical oxidation mechanism of NBOMes was explained in detail by Andrade et al 43 Briey, the rst observed oxidation peak (peak I) develops as a result of the oxidation of the secondary amine into a primary amine. Whilst, the second oxidation peak (peak II) occurs due to the replacement of the halogen atom in the NBOMe compounds by a hydroxyl group, which aerwards produces a ketone.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only few and very recently papers about blotter paper samples seizures in Brazil were published 1,9,13,[24][25][26] . The present study is a small start in the sense of to know the actual scenario of the blotter paper drug market.…”
Section: Resultsmentioning
confidence: 99%
“…Originally, phenethylamines and their derivatives, such as [2‐(4‐iodo‐2,5‐dimethoxyphenyl)‐ N ‐[(2‐methoxyphenyl)methyl]ethylamine] (25I‐NBOMe), were developed for pharmacological studies on the 5‐HT 2A receptor and for positron emission tomography (PET) imaging, respectively . Their rising popularity since 2010 as designer drugs of abuse can be traced back to the much lower costs of synthesis but similar effects compared with the better known hallucinogenic compound lysergic acid diethylamide (LSD) . LSD and NBOMe derivatives as well, are highly potent ligands and partial agonists at the 5‐HT 2A ‐receptor, which induces the typical and desired effects of these drugs .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Their rising popularity since 2010 as designer drugs of abuse can be traced back to the much lower costs of synthesis but similar effects compared with the better known hallucinogenic compound lysergic acid diethylamide (LSD). [4][5][6] LSD and NBOMe derivatives as well, are highly potent ligands and partial agonists at the 5-HT 2A -receptor, which induces the typical and desired effects of these drugs. [7][8][9] For NBOMe compounds, effects such as stimulation, euphoria, changes in consciousness and hallucinations are described.…”
Section: Introductionmentioning
confidence: 99%